Cultivation and Processing of Modern Superfood—Aronia melanocarpa (Black Chokeberry) in Slovak Republic - Ľubomír Gurčík; Zuzana Bajusová; Jana Ladvenicová; Jozef Palkovič; Katarína Novotná (Agriculture, 2023)
This scientific paper is based on the results of the research focused on the growing and processing of selected medicinal plants. Black chokeberry (Aronia melanocarpa) was included in the research because it is currently one of the most sought-after superfoods in Europe and throughout the world. Based on authentic data and literary sources, the model of economic efficiency was developed for assessment of the establishment and operation of the black chokeberry plantation in the Slovak Republic. The modelled plantation shall be spread over 10 hectares with an intensive method of cultivation (high soil quality, deep plowing, drip irrigation, fertilization with organic and inorganic fertilizer and mechanized fruit harvesting). This intensive cultivation method is characterized by higher yields in t/ha compared to an extensive cultivation method. The model is reviewed over a 12-year period. In this paper are presented three alternatives for processing total production. “Alternative A” represents the sale of the harvest to either the final consumer or the processor for further processing (fresh fruit). “Alternative B” represents the finalization of production in the form of apple–aronia juice (ratio 25% aronia–75% apple). “Alternative C” represents the finalization of production in the form of apple–aronia juice (ratio 50% aronia–50% apple).